Development of Canva-Based Interactive Media to Improve Students’ Learning Outcomes on Biodiversity Topics in Elementary School - Feranika Putri Pradana; Ipin Aripin (Ainara Journal (Jurnal Penelitian dan PKM Bidang Ilmu Pendidikan), 2026)
This study aimed to develop Canva-based interactive learning media on biodiversity topics in Natural and Social Sciences (IPAS) and to examine its feasibility, practicality, and effectiveness in improving fourth-grade students’ learning outcomes at SDN Podorejo 02. The study was motivated by the limited use of interactive learning media, which contributed to low student learning outcomes. The research employed a Research and Development (R&D) method using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The participants involved 26 fourth-grade students. Data were collected through expert validation sheets, teacher and student response questionnaires, and learning outcome tests. The validation results indicated that the media obtained scores of 91% from media experts, 90% from material experts, and 87% from language experts, with an average score of 89.3%, categorized as highly feasible. Teacher and student responses also showed a high level of practicality with an average score of 82.25%. Students’ learning outcomes improved from a pre-test average of 66.15 to a post-test average of 83.85. The paired sample t-test revealed a significant difference with t = -12.933; p < 0.001. The N-gain score of 0.5641 was categorized as moderate, with an effectiveness level of 56.41%. These findings demonstrate that Canva-based interactive learning media is feasible, practical, and moderately effective for IPAS learning in elementary schools.